2016
DOI: 10.3892/etm.2016.3881
|View full text |Cite
|
Sign up to set email alerts
|

Particularly interesting Cys-His-rich protein is highly expressed in human intracranial aneurysms and resists aneurysmal rupture

Abstract: Particularly interesting Cys-His-rich protein (PINCH) has several biological functions in cancer development, invasion and metastasis in malignant cells, and the expression of PINCH is upregulated in several cancer types, including breast cancer, gastric adenocarcinoma and rectal cancer. However, the contribution of PINCH to human cerebral aneurysms remains largely unknown. Therefore, the significance of PINCH expression in cerebral aneurysm growth and rupture was examined in the present study. The protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This was a limiting factor that we could not control, since most of the patients seen in a public service like ours, already arrive with ruptured aneurysms. Even though the study found no association between the MMP-9 levels and the rupture risk of aneurysms in these samples, the results have corroborated with those described by Peng et al [15], who showed high levels of MMP-9 in the ruptured and unruptured aneurysms when they compared them with control [15]. Other studies have also found differing MMP-9 plasma levels, but only between the ruptured aneurysms and control, with all of them having a smaller sample than the current one [7,10,11,16].…”
Section: Mmp-9 Levels In the Ruptured And Unruptured Intracranial Anesupporting
confidence: 90%
“…This was a limiting factor that we could not control, since most of the patients seen in a public service like ours, already arrive with ruptured aneurysms. Even though the study found no association between the MMP-9 levels and the rupture risk of aneurysms in these samples, the results have corroborated with those described by Peng et al [15], who showed high levels of MMP-9 in the ruptured and unruptured aneurysms when they compared them with control [15]. Other studies have also found differing MMP-9 plasma levels, but only between the ruptured aneurysms and control, with all of them having a smaller sample than the current one [7,10,11,16].…”
Section: Mmp-9 Levels In the Ruptured And Unruptured Intracranial Anesupporting
confidence: 90%
“…no. ab61682, dilution, 1:100; Abcam, Cambridge, UK), as previously described (17). Image visualization was performed under a microscope (Leica DM 2500; Leica Microsystems GmbH, Wetzlar, Germany) and the integrated optical density (IOD) was measured by Image Pro-Plus 6 software (Media Cybernetics, Inc., Rockville, MD, USA).…”
Section: Cell Counting Kit (Cck)-8 Proliferation Assaymentioning
confidence: 99%